Pre-Operative Computed Tomography Scan Assessment of Variations in Olfactory Fossa Depth among Adults - Lawal, Jamila; Nurudeen, Adebola; Quadri, Oladeji Raheem; Brai, Andrew; Dadi, Hassan Iliya; Hamza, Manir Anka (Nigerian Journal of Basic and Clinical Sciences, 2024)
ContextThe paranasal sinus Computed Tomography (CT) scan is important in the evaluation of patients with sino-nasal pathologies and serves as a tool for navigation during endoscopic sinus surgery (ESS). The risk of skull base injury during ESS is assessed using the depth of the olfactory fossa, which has been shown to have racial variations. We aimed to use Keros classification to study the variations in the depth of the olfactory fossa at a specialized tertiary ENT hospital in Kaduna, Northwest Nigeria.Setting and DesignIt was a retrospective cross-sectional study conducted at the radiology department of the National Ear Centre, Kaduna.Materials and MethodsAll CT scans of the paranasal sinuses from January 2021 – January 2022 were retrieved and reviewed. Coronal CT scans of patients, 18 years and above, were included. Those who had skull-based surgery and those with tumors of the paranasal sinuses were excluded.Statistical Analysis UsedData were entered in Statistical Product and Service Solutions (SPSS) version 25.ResultsA total of one hundred and six (106) CT scans were studied which resulted in 212 depths of olfactory fossa measurements. The age range of participants was 18–81 years with a mean age of 41.1 ± 14.18 years. The male-to-female ratio was 1:1.08. Keros type II was found to be the most prevalent (68.4%) generally, as well as across gender and laterality distribution, with statistically significant difference between males and females, and no significant difference between the right and left sides.ConclusionType II Keros classification was the most common across gender and laterality distributions, with statistically significant differences between males and females. Cognizance of individual variations in preoperative assessments and surgical planning is imperative in ensuring safe and satisfactory surgical outcomes. We recommend further studies with a larger sample size and from different regions of the country.
Keywords: Keros classification; olfactory fossa; paranasal sinus; sino-nasal pathologies